Embodied memory: Shadow and index in Family Ties by Eulàlia Valldosera. Issue 2 (June 2019) - Bru-Domínguez, Eva
Abstract : This article explores questions of memory and corporeal trace in the photographic series Family Ties (2012) by Catalan visual and performance artist Eulàlia Valldosera. It situates her work in relation to the formal and conceptual shift in art that took place in the international arena in the 1960s, and that was characterized by a disregard for the material art-object and a turn to ephemeral, conceptual, and performative artistic practices. Focusing on the concept of index (as bodily trace) and shadow (as the materialization and/or visualization of the subject's unconscious), the article analyses Valldosera's use of these two recurrent motifs in the visual arts as a means of engaging with the omissions and discontinuities of her most immediate cultural and historical context. In so doing, it shows how traces of past bodily relations in space – past instances in the construction of the self – are activated, performed, and materialized through the body.